Assaying macrophage activity in a murine model of inflammatory bowel disease using fluorine-19 MRI - Kadayakkara, Deepak K (2012)
Macrophages have an important role in the pathogenesis of most chronic inflammatory diseases. A means of non-invasively quantifying macrophage migration would contribute significantly towards our understanding of chronic inflammatory processes and aid the evaluation of novel therapeutic strategies. We describe the use of a perfluorocarbon tracer reagent and in vivo (19)F magnetic resonance imaging (MRI) to quantify macrophage burden longitudinally. We apply these methods to evaluate the severity and three-dimensional distribution of macrophages in a murine model of inflammatory bowel disease (IBD). MRI results were validated by histological analysis, immunofluorescence and quantitative real-time polymerase chain reaction. Selective depletion of macrophages in vivo was also performed, further validating that macrophage accumulation of perfluorocarbon tracers was the basis of (19)F MRI signals observed in the bowel. We tested the effects of two common clinical drugs, dexamethasone and cyclosporine A, on IBD progression. Whereas cyclosporine A provided mild therapeutic effect, unexpectedly dexamethasone enhanced colon inflammation, especially in the descending colon. Overall, (19)F MRI can be used to evaluate early-stage inflammation in IBD and is suitable for evaluating putative therapeutics. Due to its high macrophage specificity and quantitative ability, we envisage (19)F MRI having an important role in evaluating a wide range of chronic inflammatory conditions mediated by macrophages.